Highly sensitive colour change system within slight differences in metal ion concentrations based on homo–binuclear complex formation equilibrium for visual threshold detection of trace metal ions - Mizuguchi, Hitoshi; Atsumi, Hiroshi; Hashimoto, Keigo; Shimada, Yasuhiro; Kudo, Yuki; Endo, Masatoshi; Yokota, Fumihiko; Shida, Junichi; Yotsuyanagi, Takao (Analytica chimica acta, 2004)
A new technique of expressing slight differences in metal ion concentrations by clear difference in colour was established for visual threshold detection of trace metal ions. The proposed method is based on rapid change of the mole fraction of the homo–binuclear complex (M 2L) about a ligand in a narrow range of the total metal ion concentration ( M T) in a small excess, in case the second metal ion is bound to the reagent molecule which can bind two metal ions. Theoretical simulations showed that the highly sensitive colour change within slight differences in metal ion concentrations would be realized under the following conditions: (i) both of the stepwise formation constants of complex species are sufficiently large; (ii) the stepwise formation constant of the 1:1 complex (ML) is larger than that of M 2L; and (iii) the absorption spectrum of M 2L is far apart from the other species in the visible region. Furthermore, the boundary of the colour region in M T would be readily controlled by the total ligand concentration ( L T). Based on this theory, the proposed model was verified with the 3,3′-bis[bis(carboxymethyl)amino]methyl derivatives of sulphonephthalein dyes such as xylenol orange (XO), methylthymol blue (MTB), and methylxylenol blue (MXB), which can bind two metal ions at both ends of a π-electron conjugated system. The above-mentioned model was proved with the iron(III)–XO system at pH 2. In addition, MTB and MXB were suitable reagents for the visual threshold detection of trivalent metal ions such as iron(III), aluminium(III), gallium(III) and indium(III) ion in slightly acidic media. The proposed method has been applied successfully as a screening test for aluminium(III) ion in river water sampled at the downstream area of an old mine.